The Integration of Community-Based Tourism into the Creative Economy in the Development of Woven Fabrics: A Case Study of the Traditional Village of Prai Ijing, West Sumba - Alsya Putra, Daffa; Syarifuddin Latif, B (Journal Research of Social Science, Economics, and Management, 2026)
The integration of local cultural heritage with sustainable tourism has become a strategic approach to improve community welfare while preserving traditional values. However, many traditional villages still face challenges in developing creative economy products such as woven fabrics through a community-based approach. This research aims to analyze the development strategy of a woven fabric-based creative economy through a Community-Based Tourism (CBT) approach in the Prai Ijing Traditional Village, West Sumba. The research used a qualitative method with a case study approach. Data were collected and analyzed based on observations, documentation, digital analysis through SWOT analysis, and a development strategy plan. The results show that strengthening community capacity, product diversification, integration with the tourism sector, and digitalization of marketing are the main strategies in developing a woven fabric-based creative economy. This research confirms that the CBT approach plays a crucial role in improving community welfare while maintaining the sustainability of local culture. The contribution of this research lies in the integration of the CBT model and a local culture-based creative economy as a strategy for sustainable tourism development in traditional areas.